142k views
3 votes
Prove cos^4 X +sin^4 x= 2cos^2 x for any acute angle​

Prove cos^4 X +sin^4 x= 2cos^2 x for any acute angle​-example-1
User Morg
by
4.8k points

2 Answers

7 votes

To prove cos^4x-sin^4x +1= 2 cos^2 x

cos^4x -sin^4 x+1

= ( cos^2x +sin^2x)(cos^2x - sin^2x) +1

You need to remember 3 basic results

sin^2x + cos^2x= 1

cos2x = cos^2x - sin^2x

1+ cos 2x = 2 cos^2x

Now Let's revert back to question

= ( cos^2x + sin^2x )( cos^2x - sin^2x) +1

= 1( cos2x) +1

= cos2x +1

= 2 cos^2x

User HonzaB
by
5.8k points
5 votes

Answer:

Proof provided in the explanation.

Explanation:


\cos^4(\theta)-\sin^4(\theta)+1

I'm going to rewrite that middle term so I can apply Pythagorean Identity,
\sin^2(\theta)=1-\cos^2(\theta):


\cos^4(\theta)-(\sin^2(\theta))^2+1


\cos^4(\theta)-(1-\cos^2(\theta))^2+1

Use
(a+b)^2=a^2+2ab+b^2:


\cos^4(\theta)-[1-2\cos^2(\theta)+\cos^4(\theta)]+1

Distribute:


\cos^4(\theta)-1+2\cos^2(\theta)-\cos^4(\theta)+1

Combine like terms:


\cos^4(\theta)-\cos^4(\theta)-1+1+2\cos^2(\theta)

Applying inverse property of addition:


0+0+2\cos^2(\theta)

Applying identity property of addition:


2\cos^2(\theta)

User RedCrusador
by
4.9k points